Regulation and roles of bicarbonate transport in cancer - Gorbatenko, Andrej; Olesen, Christina W.; Boedtkjer, Ebbe; Pedersen, Stine F. (Frontiers in Physiology, 2014)
A unifying feature of solid tumors is a markedly altered pH profile compared to normal tissues. This reflects that solid tumors, despite completely different origins, often share several phenotypic properties with implications for intra- and extracellular pH. These include: a metabolic shift in most cancer cells towards more acid-producing pathways, reflecting both oncogenic signaling and the development of hypoxia in poorly perfused regions of the tumors; the poorly perfused and often highly dense tumor microenvironment, reducing the diffusive flux of acid equivalents compared to that in normal tissues; and the markedly altered regulation of the expression and activity of pH-regulatory transport proteins in the cancer cells. While some of these properties of tumors have been well described in recent years, the great majority of the research in this clinically important area has focused on proton transport, in particular via the Na+/H+-exchanger 1 (SLC9A1, NHE1) and various H+ ATPases. We have, however, recently demonstrated that at least under some conditions, including in vitro models of HER2 positive breast cancer, and measurements obtained directly in freshly dissected human mammary tumors, bicarbonate transporters such as the electroneutral Na+,HCO3–cotransporter (SLC4A7, NBCn1), are upregulated and play central roles in pH regulation. In this review, we summarize and discuss the current knowledge regarding the regulation and roles of bicarbonate transport in cancer.